Convergent validity of K-SADS-PL by comparison with CBCL in a Portuguese speaking outpatient population - Bordin Isabel A; Brasil Heloisa HA (BMC Psychiatry, 2010)
Abstract Background Different diagnostic interviews in child and adolescent psychiatry have been developed in English but valid translations of instruments to other languages are still scarce especially in developing countries, limiting the comparison of child mental health data across different cultures. The present study aims to examine the convergent validity of the Brazilian version of the Schedule for Affective Disorders and Schizophrenia for School-Age Children/Present and Lifetime Version (K-SADS-PL) by comparison with the Child Behavior Checklist (CBCL), a parental screening measure for child/adolescent emotional/behavior problems. Methods An experienced child psychiatrist blind to CBCL results applied the K-SADS-PL to a consecutive sample of 78 children (6-14 years) referred to a public child mental health outpatient clinic (response rate = 75%). Three K-SADS-PL parameters were considered regarding current disorders: parent screen interview rates, clinician summary screen interview rates, and final DSM-IV diagnoses. Subjects were classified according to the presence/absence of any affective/anxiety disorder, any disruptive disorder, and any psychiatric disorder based on K-SADS-PL results. All subjects obtained T-scores on CBCL scales (internalizing, externalizing, total problems). Results Significant differences in CBCL mean T-scores were observed between disordered and non-disordered children. Compared to children who screened negative, children positive for any affective/anxiety disorder, any disruptive disorder, and any psychiatric disorder had a higher internalizing, externalizing and total problem T-score mean, respectively. Highly significant differences in T-score means were also found when examining final diagnoses, except for any affective/anxiety disorder. Conclusions Evidence of convergent validity was found when comparing K-SADS-PL results with CBCL data.